Front Cover: Ellagic Acid and Its Microbial Metabolite Urolithin A Alleviate Diet‐Induced Insulin Resistance in Mice. Issue 19 (2nd October 2020) - Yang, Jieping; Guo, Yuanqiang; Henning, Susanne M.; Chan, Brenda; Long, Jianfeng; Zhong, Jin; Acin‐Perez, Rebeca; Petcherski, Anton; Shirihai, Orian; Heber, David; Li, Zhaoping
Abstract : Mol. Nutr. Food Res . 2020, 64, 2000091 DOI: 10.1002/mnfr.202000091 Large inter‐individual variation of microbial conversion of ellagic acid (EA) into urolithin A (UA) is known in humans. EA and UA intake result in differential metabolic benefits and mitochondrial dynamics in insulin resistant mice. These data suggest that individuals capable of UA production will experience the most benefits of EA intake in regards to glucose metabolism and mitochondrial health. This is reported by Jieping Yang, Yuanqiang Guo, Susanne M. Henning, Brenda Chan, Jianfeng Long, Jin Zhong, Rebeca Acin‐Perez, Anton Petcherski, Orian Shirihai, David Heber, Zhaoping Li in article 2000091 .